Progression of Spinal Ligament Ossification in Patients with Thoracic Myelopathy - Jiliang Zhai; Shigong Guo; Jiahao Li; Bingrong Chen; Yu Zhao (Orthopaedic Surgery, 2022)
Objective To evaluate the rate of increase in thickness and cross‐section area (CSA) of the ossification in thoracic myelopathy with or without cervical and lumbar spinal ligament ossification. Methods A total of 24 patients with 170 segments (47 ligamentum flavum [OLF] and 123 cases of ossification of the posterior longitudinal ligament [OPLL]) of spinal ligament ossification between January 2012 and March 2019 at a single institution were retrospectively reviewed. Demographic data, classification of OPLL, Sato classification of OLF, pre‐ and postoperative neurological function and complications were recorded. The thickness and CSA at the segment of maximum compression were measured with Image J software on the axial CT image. Results Twelve female and 12 male patients with thoracic myelopathy and spinal ligament ossification were enrolled in the study. The mean age of the patients was 54.0 ± 11.9 years with an average follow‐up of 22.2 ± 23.5 months. Overall, the mean rate of progression in thickness and CSA was 1.2 ± 1.6 and 18.4 ± 50.6 mm2/year, respectively. Being female, aging (≥45 years), and lower BMI (<28 kg/m2) predisposed patients to have faster ossification growth in thickness and CSA. The difference between the rate of OPLL and OLF progression in thickness and CSA was not significant. However, the rate of OPLL progression in the thoracic spine was significantly higher than that in the cervical spine regarding thickness (1.4 ± 1.9 vs. 0.6 ± 0.7 mm/year) and CSA (27.7 ± 72.0 vs. 7.3 ± 10.3 mm2/year). Conclusion This is the first study to investigate ligament ossification progression in patients with thoracic myelopathy. The difference between the rate of OPLL and OLF progression in thickness and CSA was not significant. However, the rate of thoracic OPLL progression in thickness and CSA was significantly higher than that in the cervical spine.